Pengaruh Karakteristik Bintang Iklan dan E-Commerce terhadap Minat Beli Ulang Produk Fashion di Kota Madya Madiun - Endang Edi Rahayu (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2018)
The number of internet users is increasing, thus causing the rise of people buying online. Marketing via online is considered more practical and more attractive consumer.Online shopping is a relatively new thing in Indonesia.Konsumen feel the need to find information about the product offered.One product offered is a fashion product.Pemilihan celebrities as endoser is considered will affect the interest of purchase . Then the company must really understand the characteristics of celebrities that are used as advertising stars. The results show that partially and simultaneously, the characteristics of advertising and e-commerce stars have a significant effect on the interest of buy back of fashion products. And the dominant factor is e-commerce.Keyword: Advertising Star Characteristics, E-Commerce, Interest Of Buy Back of Fashion Product.